(untitled) (Research, Society and Development, 2022)
The present integrative review research aimed to investigate the profile and aspects of body composition and the prevalence of lower limb sports injuries in male basketball athletes. It was searched in the electronic Portal BVS, PubMED, LILACS and SCIELO with the descriptors: body composition, injuries and basketball. We included the findings that: addressed the problematic of the study (body composition and sports injuries in lower limbs in male basketball athletes) by bringing in the title, abstract, subject, key words or full text the descriptors selected for this review; were published from 2017 to 2022 in Portuguese, English and/or Spanish; and were complete publications. With the descriptors used and the search and selection strategies, this review resulted in 6 articles selected after applying the inclusion and exclusion criteria. The profile of body composition aspects and the prevalence of lower limb sports injuries in male basketball athletes presents several contexts for discussion, and in this scenario, an incipient relationship between body composition in athletes and lower limb sports injuries was evidenced. The state of the art, still with scarce productions, evidenced a prevalence profile of sports injuries in lower limbs in these athletes, mainly related to the composition of muscle mass and body fat.